The Uncertainty in Family Medicine Training - Claramita, Mora; Irawati, Yulia Dewi (Faculty of Medicine, Public Health, and Nursing, 2024)
Ever since we heard about family medicine training, there have been lots of differences within the context of primary care compared to the specialization in the hospital’s settings. One of them is the ‘uncertainty.’ The uncertainty of health care started from the process of development of diagnosis because of the first contact nature of patients in primary care settings with possible signs and symptoms can lead to number of diseases1. A cough symptom can be uncomplicated influenza, a very sign of the start of an epidemic, or signs of a more contagious severe illness like Tuberculosis, or a non-infectious problem but can be life-threatening for the patient. We also still need to consider the ‘illnesses’ so that the patients can have their perceptions regarding the health problems and the treatment they should receive. At this point, two-way dialogue to overcome the uncertainty in handling health problems is the key to understanding patients’ perspectives. Only by understanding patients’ perspectives can family doctors work together with the patient to approach a more suitable treatment and health care planning.